Case report: Exceptional transmission of congenital hyperinsulinism from a focal CHI mother to her diffuse CHI dichorionic diamniotic twins - Telehuz, Daniela; Plesa, Oana; Bouilloud, Florence; Wucher, Helene; De Lonlay, Pascale; Bérat, Claire-Marine; Saint-Martin, Cécile; Dupuy, Olivier; Arnoux, Jean-Baptiste (Frontiers in Endocrinology, 2024)
We present the case of a 36-year-old female who was diagnosed at birth with CHI that caused severe hypoglycaemia unresponsive to Diazoxide. Subtotal pancreatectomy was performed at the age of three weeks. Later, histological analysis of her pancreas in a research setting revealed a focal form of CHI. Genetic testing was not available at that time. The patient developed pancreatic exocrine deficiency and insulin-dependent diabetes at the age of 9 years.In 2016, a genetic test revealed a missense heterozygous variant in the ABCC8 gene inherited from her father and classified as having a recessive inheritance. The geneticist concluded that the risk of CHI for her offspring would be low (1/600), making pregnancy favourable. As there was no consanguinity in the family, testing the future father was deemed unnecessary (carrier frequency 1/150 in the general population).The pregnancy occurred spontaneously in 2020 and at a gestational age of 28 weeks, the mother went into premature labour. An emergency C-section was performed in April 2021 resulting in the birth of bichorial bi-amniotic male twins. Following birth, both newborns experienced persistent severe hypoglycaemia which required glucagon treatment and intravenous glucose infusion initially, followed by Diazoxide from day 51 after birth, without satisfactory response. Continuous intravenous Octreotide treatment was introduced on day 72. Due to the recurrence of hypoglycaemia episodes despite reaching maximum doses of Octreotide, from day 92 the treatment was switched to Pasireotide.Genetic tests revealed the same genotypes for both infants: the exon 39 missense variant (c.4716C>A; p.Ser1572Arg) inherited from their mother and a truncating variant in exon 28 (c.3550del; p.Val1184*), inherited from their asymptomatic father. As a result of inheriting two recessive variants of the ABCC8 gene, the children were diagnosed with a diffuse form of CHI, consistent with the diazoxideunresponsive presentation. This situation is very rare outside consanguinity. This case emphasises the significance of genetic counselling for individuals with a history of rare diseases outside the context of consanguinity, as there is a potential risk of recurrence. Prenatal diagnosis can lead to better outcomes for affected neonates, as well as help families make informed decisions about future pregnancies.